Effectiveness of theory-based educational interventions of promoting oral health among elementary school students - Samane Shirahmadi; Saeed Bashirian; Ali Reza Soltanian; Akram Karimi-shahanjarini; Farshid Vahdatinia (BMC, 2024)
Abstract Background The aim of the present study was to determine the effect of oral health education programs on the oral health of primary school students. Methods In this randomized controlled trial study, 190 elementary fifth-grade female students were chosen using the multistage cluster sampling method. In this study, the Plaque Index (PI), Simplified Oral Hygiene Index (OHI-S), Community Periodontal Index (CPI), tooth brushing using fluoride toothpaste, dental flossing frequency and factors affecting them were determined according to social cognitive theory (SCT). Interventions were implemented using the play method and with the help of three pamphlets, five posters, a celebration of oral health, and the creation of a Telegram group. Data were analyzed using descriptive statistics indexes, t tests, paired sample t tests, chi-square tests, and Pearson correlation tests. Results The results showed that 3 months after the intervention, compared to before the intervention, the percentage of participants in the intervention group who brushed their teeth twice or more per day increased by 48.5%, and the percentage of participants who used dental floss at least once per day increased by 64.2%. The rate of gum bleeding decreased by 6.3%. The good OHI-S rate increased by 44.4%. Dental plaque decreased by 38.1%. Conclusion The results demonstrated that a gamification design can be effective and useful in promoting the oral health of students. Trial registration registration timing: retrospective, registration date: 18/10/2022, registration number: IRCT20141128020129N2.